Desain Video Animasi Berbasis Studi Kasus Untuk Mata Kuliah Pengembangan E-Learning - Silvia Rahmadini; Ulfia Rahmi (Universitas Negeri Padang, 2022)
Based on what happened in the field, it is known that the content developed in the video still has a weakness, namely the content developed is still conceptual. However, it is also expected that students can understand contextually. Contextual learning can make students more active because students try to learn concepts as well as apply and relate them to the real world. Making students more active in the learning process can occur if students are involved in the learning process. So, the purpose of designing this animated video is so that students feel firsthand the problems that occur in the field and students have a contextual understanding. In addition, so that this video media can be developed later. The research was conducted with a descriptive research design. The design of an animated video media is followed by media validation, then the media can be used in blended learning in e-learning development courses. The design activities carried out include 3, namely; design of video content in e-learning development courses; design of case study-based teaching material content; and designing animated videos with case study-based teaching material content. The design of case study-based animated video media by developing appropriate learning content can increase student involvement in the learning process and improve contextual understanding. From the results obtained, it can be concluded that the case study-based animation video media that has been designed is feasible to be used and developed in e-learning development courses